2013
DOI: 10.1371/journal.pone.0070160
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Gains in Visuospatial Memory Predict Gains in Mathematics Achievement

Abstract: Visuospatial competencies are related to performance in mathematical domains in adulthood, but are not consistently related to mathematics achievement in children. We confirmed the latter for first graders and demonstrated that children who show above average first-to-fifth grade gains in visuospatial memory have an advantage over other children in mathematics. The study involved the assessment of the mathematics and reading achievement of 177 children in kindergarten to fifth grade, inclusive, and their worki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
87
1
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(100 citation statements)
references
References 55 publications
5
87
1
7
Order By: Relevance
“…This revealed that there were no significant differences in the regression estimates for the separate measures, which suggests that verbal and visuo-spatial working memory play a similar role, in young children at least. There is some evidence that younger and older children may rely on different forms of working memory (Li & Geary, 2013, although see Cragg et al, 2017 and so this pattern should be tested further with older children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This revealed that there were no significant differences in the regression estimates for the separate measures, which suggests that verbal and visuo-spatial working memory play a similar role, in young children at least. There is some evidence that younger and older children may rely on different forms of working memory (Li & Geary, 2013, although see Cragg et al, 2017 and so this pattern should be tested further with older children.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of research has focused on working memory, the ability to monitor and manipulate information held in mind, and revealed that this is related to both concurrent and future mathematics achievement across development (see reviews by Bull & Lee, 2014;Raghubar, Barnes, & Hecht, 2010). Associations with mathematics achievement have been found for both verbal and visuo-spatial working memory, although there is mixed evidence regarding which is more important (Friso-van den Bos, van der Ven, Kroesbergen, & van Luit, 2013;Szucs, Devine, Soltesz, Nobes, & Gabriel, 2013), which could be explained by developmental changes (Li & Geary, 2013). Working memory has been found to be associated both with general measures of overall mathematics achievement and individual components of mathematics (Cragg, Keeble, Richardson, Roome, & Gilmore, 2017;Friso-van den Bos et al, 2013).…”
Section: Working Memorymentioning
confidence: 99%
“…Diferentes estudios informan que la MT parece estar relacionada con el aprendizaje matemático y la aparición de dificultades (Li y Geary, 2013;Swanson y Jerman, 2006). No obstante, esa relación no siempre es fácil de interpretar.…”
Section: Introductionunclassified
“…Another difference between the two measures is that CBM scoring is more sensitive to developing skill, as any correct number that appears in the answer merits one point. Therefore, it follows to reason that the influences of inattention on higher-level math outcomes, which require more attention to algorithm and less reliance on fluent retrieval, are partially accounted for by WM ability, in the visual-spatial domain that is consistently linked to math outcomes (Alloway & Passolunghi, 2011;Li & Geary, 2013;Rogers et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Differential influences of visual-spatial and auditory-verbal WM are of interest, given previous research that implicates visual-spatial WM as an important factor in math achievement in elementary and high school, and previous findings of differential relationships between WM domain and achievement domain (Li & Geary, 2013;Rogers et al, 2011). Based on the described previous studies as well as on examination of this sample within a 1 year time frame (Gray, Rogers, Martinussen, & Tannock, submitted manuscript), it is hypothesized that there will be a direct relationship between classroom inattention at one point in time and both math and reading outcomes one year later.…”
mentioning
confidence: 99%